The Next Great War? : The Roots of World War I and the Risk of U.S.-China Conflict - Miller, Steven E.; Rosecrance, Richard N. (Book collections on Project MUSE., 2014)
Experts consider how the lessons of World War I can help prevent U.S.--China conflict.